The intention to quit apprenticeships and the role of secondary jobs - Seidel, Katja [Verfasser] (My University, 2019)
"This paper analyses the effect of a secondary job on the intention to quit an apprenticeship in Germany. For the empirical approach, the representative German, firm-level study 'BIBB Survey Vocational Training from the Trainees Point of View 2008' conducted by the Federal Institute for Vocational Education and Training (BIBB) is used. In this study, 5901 apprentices were interviewed during their second year of apprenticeship. To date, literature on early contract cancellation in Vocational Education and Training uses income itself as a determinant, but neglects the consequences of low income during apprenticeship, such as the need for a secondary job and possible secondary-job-related burdens. The probit regressions show a higher intention to quit if apprentices require a secondary job to cover their living costs." (author's abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); Berufsausbildung; Ausbildungsabbruch; Ausbildungswechsel; Nebentätigkeit; Einflussfaktor